Comparative efficacy of intralesional triamcinolone acetonide injection during early and static stage of pathological scarring. (22nd June 2018) - Song, Huapei; Tan, Jianglin; Fu, Qingqing; Huang, Ling; Ao, Ming
Summary: Objective: This study aims to clarify whether the effect of intralesional triamcinolone acetonide injection during the early stage of scarring differs from the static stage, which still remains unclear. Methods: A total of 108 patients with pathological scars were enrolled in this study and were divided into 2 groups according to the time of first treatment after injury: the early stage group(≤6 months after injury) and the static stage group(>6 months after injury). Patients of both groups were then treated with intralesional triamcinolone acetonide injection. The Vancouver scar scale was adopted for the evaluation of scars, and a durometer was utilized for the measurement of the hardness of the scar. The visual analog scale was adopted for the assessment of patients' subjective feelings (pruritus and pain). In the meantime, adverse drug reactions were also recorded. Results: After intralesional injection of triamcinolone acetonide, most of the hypertrophic scars and keloids improved in color, thickness, softness, and vascular distribution. The hardness of scars improved significantly. The overall efficacy of the static stage group was superior to the early stage group. Most patients, after the injection of triamcinolone acetonide, had significant alleviation or even total loss of cicatricial pain and pruritus. Conclusions: This study demonstrates that the treatment efficacy was better when applied during the static stage of pathological scarring rather than the early stage, which might be due to macrophages and their released cytokines. This study provides new clinical evidence for optimizing drug therapy of pathological scars.